Poppað bygg. Eiginleikar og vöruþróun - Braga Stefaný Mileris 1991- (2018)
Barley is the only cereal that can be grown in the climate conditions in Iceland. Most of it is used as animal feed but there is a growing interest in using it in food products. The aim of the project was to develop healthy food products based on Icelandic barley. Stepwise product development was used in the project. Brain storming and screening of ideas resulted in focusing on popping the barley to improve palatability and digestibility. Various types of whole and polished barley grains were screened using different methods of popping. One method was optimized resulting in a popped barley that was used for developing muesli products. Popped barley was analyzed for nutritional value, fiber, β glucans as well as safety, stability, organoleptic properties and shelf life by chemical, physical, microbial and sensory methods. The popped barley was high in fiber (10.8 gr), β glucans (3.8 gr) and protein (13.3 gr) but low in fat (1.2 gr.). Very low water activity (0.2 aw) played a part in an estimated shelf life of 4 months that was confirmed by the results of the microbial and sensory analysis. Prototypes of popped barley based muesli products were tested by consumers in Iceland and by a panel of juries both in the Icelandic and European Ecotrophelia competitions on ecofriendly food products. The feedback received was used to improve the palatability and quality of the products. One of the improvements was to make small clusters of the popped barley grains. Study on the effects of the amount of added syrups and sugar replacers on crunchiness and cohesiveness were studied ending in selecting an acceptable product by the producers of Arctic Barley. The popping process of barley was optimized. Semi-popped barley was mixed with other ingredients and processed into muesli products with or without clusters and even some other unforeseen products. There are opportunities in turning the developed products into business opportunities to benefit consumers in Iceland and other countries. Bygg er eina kornið sem hægt er að ...